A Three-Dimensional Representation of the Piles Radio Image on the Radargram for the Completed Construction - Odilavadze, Davit T.; Chelidze, Tamaz L.; Yavolovskaya, Olga V. (Journals of Georgian Geophysical Society, 2025)
One of the important issues in urban geolocation is the determination of the depth of piles within the scope of geolocation activity. The peculiarity of the complexity of the issue lies in the heterogeneity of the work environment, which can be found both in an open space, such as a construction site, and in a closed, i.e. completed and put into operation building. Conducting geolocation profiles under operational building conditions is also limited due to existing partitions and architectural elements of non-conducive placement. In some cases, we are forced to limit ourselves by taking partial profiles and use a complicated interpretation for such a radargram. In particular, we additionally use the three-dimensional spatial representation for the intersections of geolocation profiles to determine the depth of the target pile. For the interpretation of the depth limit of pile, it is recommended to fix the location of the hyperbola of the pile radio image on the axis of intersection of the intersecting profiles for both profiles, to imagine and interpret the 3D radio image of the target pile for the intersection axis of the profiles.